Remaking the border: the proposed border expansion of Canberra in the 1960–70s revisited in the planning and development context of the 21st century. (4th March 2021) - Hu, Richard
ABSTRACT: In the 1960–70s, there was a proposal to expand the administrative border of Canberra into the neighbouring state New South Wales to accommodate long-term population growth and urban development. However, this attempt failed ultimately. This study investigates this 'remaking' of the border, and revisits the same issue in the planning and development context of the twenty-first century. It employs three conceptual constructs – 'bordering', 'debording', and 'rebordering' – to draw insights into the nexus between the border's (re)making, dominant planning thinking, and emerging development process. It uses a mix of primary and secondary sources of data and information collected from the National Archives of Australia, newspaper clippings of The Canberra Times, interviews with planners involved, Australian Census data, and planning literature. It finds that the border expansion proposal was driven by a political advocacy out of a modernist technocratic planning vision for a linear city, and was based on an over-optimistic and mechanical population projection. However, as a highly political initiative, its failure was doomed by political strains and changes, and local community's concerns. Knowing this history contributes to tackling a similar issue in today's paradox of a planning paradigm for compactness and sustainability and an emerging development expansion onto the border.